Factors of family impact in a Swedish–German cohort of children born with esophageal atresia - Michaela Dellenmark-Blom; Kate Abrahamsson; Jens Dingemann; Stefanie Witt; Carmen Dingemann; Linus Jönsson; Vladimir Gatzinsky; Monika Bullinger; Benno M. Ure; John E. Chaplin; Julia H. Quitmann (Orphanet Journal of Rare Diseases, 2022)
Abstract Background After repair of esophageal atresia (EA), childhood survivors commonly present with digestive and respiratory morbidity, and around 55% have associated anomalies. Although it is known that these problems can reduce health-related quality of life in children with EA, less is understood about the impact on the family. We aimed to identify factors related to family impact in children with EA. Methods One parent each of a child with EA (2–18 years) in 180 families from Sweden and Germany answered the PedsQL™ Family Impact Module as the dependent variable. The independent variables were the child’s parent-reported health-related quality of life as measured by PedsQL™ 4.0, current symptoms, school situation, and parent/family characteristics together with child clinical data from the medical records. Results Stepwise multivariable regression analysis showed a multifactorial model of the total family impact scores (R 2 = 0.60), with independent factors being the child’s overall generic health-related quality of life, school-absence ≥ 1/month, severe tracheomalacia, a family receiving carer’s allowance, and a parent with no university/college education, p < 0.05. Logistic regression analysis showed that an increased number of symptoms in the child the preceding 4 weeks lowered the family impact scores; however, the child’s feeding (R 2 = 0.35) and digestive symptoms (R 2 = 0.25) explained more in the variation of scores than the child’s respiratory symptoms (R 2 = 0.09), p < 0.0001. Conclusions Family functioning may be a contributing factor to the maintenance of child health. The study findings suggest multifactorial explanations to family impact in children with EA, which are essential when optimizing the support to these families in clinical and psychosocial practice. Future research should explore experiences of family impact from all family members’ perspectives and multicenter studies are warranted to understand better the effectiveness of psychosocial-educational interventions to families of children with EA.